2018
DOI: 10.1111/dme.13605
|View full text |Cite
|
Sign up to set email alerts
|

Development of a screening tool using electronic health records for undiagnosed Type 2 diabetes mellitus and impaired fasting glucose detection in the Slovenian population

Abstract: This study proposes two simplified models based on FINDRISC questions for screening of undiagnosed Type 2 diabetes and impaired fasting glucose in the Slovenian population. A significant improvement in performance was achieved compared with the original FINDRISC questionnaire. Both models include waist circumference instead of BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
1
21
1
Order By: Relevance
“…Similar results were found in the previous research conducted in Slovenia 17 , where the most important variables were hyperglycemia history, gender, age, physical activity, waist circumference, (BMI), diabetes in family, fruit and vegetables consumption and antihypertensive drugs. Variables as age, parental history of diabetes and BMI were statistically significant predictors of T2DM already in The Framingham Offspring Study 39 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results were found in the previous research conducted in Slovenia 17 , where the most important variables were hyperglycemia history, gender, age, physical activity, waist circumference, (BMI), diabetes in family, fruit and vegetables consumption and antihypertensive drugs. Variables as age, parental history of diabetes and BMI were statistically significant predictors of T2DM already in The Framingham Offspring Study 39 .…”
Section: Discussionsupporting
confidence: 91%
“…Initially, the dataset consisted of 111 variables including a group of variables related to the FINDRISC (FR) questionnaire 16 such as variables representing physical activity (at least 30 min during the day), fruit and vegetable consumption as well as keeping a track of medical history including the history of antihypertensive drug treatment, history of high blood glucose levels and family history of diabetes. Consequently, all cases with any missing FR variable were removed from the dataset to allow comparison to the FR-based model that was developed for Slovenian population by Stiglic et al 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for the age component of the tool, several Caucasian studies have reported a mean age greater than that of our study [12,19,21,36]. This increase in age could lead to an increase in the risk score in this population [12,21,47,49]. Several studies conducted in South Africa have suggested threshold values of waist circumference different from those currently used for African populations [50][51][52].…”
Section: Optimal Threshold For the Prediction Of Type2 Diabetes With contrasting
confidence: 51%
“…In addition, the threshold used in Caucasians studies, which ranges from 11 to 15 in most FINDRISC questionnaire validation studies is higher than that of our study. Optimal thresholds used were higher or equal to 11 [20,21,[47][48][49].…”
Section: Optimal Threshold For the Prediction Of Type2 Diabetes With mentioning
confidence: 99%